Penerapan ARIMA Pada Data Curah Hujan di Stasiun Meteorologi Kelas II Minangkabau Padang Pariaman - Nur, Rizki Amalia; Putri, Darvi Mailisa (JOSTECH Journal of Science and Technology, 2024)
Rainfall is one of the indicators of climate change that has an impact. Class II Minangkabau Meteorological Station Padang Pariaman is one of the locations that has an impact on rainfall. This location is Minangkabau International Airport so that rainfall information is very important. The rainfall data used in this study is monthly data with the period January 2017 to June 2022. The ARIMA model is applied to perform forecasting or prediction of rainfall data for the next period. The results of the study based on the analysis of the Akaike Information Criterion (AIC) value obtained the best model ARIMA (3,1,0).